An Observational Study on The Role of Magnetic Resonance Imaging in The Evaluation of Soft Tissue Tumors with Histopathological Correlation at Tertiary Care Centre - Sriramula Sripriya; Tejaswini Mogalagunta; Sunitha Bajaj; Sudha Bindu T; Madhavi T (Health Technology Assessment in Action)
Background: The primary aim of this study is to evaluate the role of magnetic resonance imaging (MRI) in the assessment of soft tissue tumors with histopathological correlation at a tertiary care center. Methods: An observational study was conducted on 75 patients (n = 75) in the Department of Radiodiagnosis over 18 months. The targeted population comprised patients who presented to the Radiodiagnosis Department for radiological imaging of soft tissue tumors. Results: Out of 75 cases, 20% were found to have benign tumors, while 80% were found to have malignant tumors. The most frequent benign tumor was fibromatosis, with n = 10 cases (13.33%), and the most common malignant tumor was synovial sarcoma, with n = 14 cases (18.66%). The benign age group ranged from 11 to 20 years. T2-weighted heterogeneous hyperintensity was noted more frequently in malignant lesions, demonstrating a high positive predictive value; that is, 83% of malignant tumors exhibited changes on diffusion-weighted imaging/ apparent diffusion co efficient (DWI/ADC). Low-grade malignant lesions showed no restrictions. Most benign lesions displayed restrictions, with a high positive predictive value of 98.14%, specificity of 93.33%, and sensitivity of 88.33%. Conclusions: Soft tissue tumors can be detected and locally staged using MRI; thus, this technique has proven its value. Intralesional hemorrhage and calcification are two parameters that have been shown to have no substantial association with cancer. Due to its high sensitivity, MRI is a viable option for evaluating soft tissue tumors.